2020
DOI: 10.1016/j.heliyon.2020.e05193
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of pathological and clinical characteristics of cervical conization according to age group in Japan

Abstract: Objective With increased screening, more patients with precancerous or early cervical cancer are now being identified. Age at pregnancy, and thus number of patients requiring fertility preservation, have also increased, resulting in more diagnostic and therapeutic cervical conization (conization) procedures. We here investigated the pathological and clinical characteristics of patients undergoing conization, with a focus on age. The objectives of our study were to identify the risk factors potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 38 publications
3
14
0
1
Order By: Relevance
“…Our study reported several risk factors for cervical cancer recurrence, including younger age, lower parity, a greater number of miscarriages, higher clinical stage, lymph node metastasis, and received chemotherapy, and we found that miscarriage, clinical stage, and treatment received remained significant in the adjusted Cox regression model. These risk factors identified have also been reported by previous studies 4 , 20 . Clinical stage was the most commonly reported risk factor for cancer recurrence 19 , 21 , 22 , our study results showed that patients with clinical stage II had 1.73 times the risk of recurrence, and patients with stage III or IV had 2.04 times the risk compared to those with clinical stage I.…”
Section: Discussionsupporting
confidence: 89%
“…Our study reported several risk factors for cervical cancer recurrence, including younger age, lower parity, a greater number of miscarriages, higher clinical stage, lymph node metastasis, and received chemotherapy, and we found that miscarriage, clinical stage, and treatment received remained significant in the adjusted Cox regression model. These risk factors identified have also been reported by previous studies 4 , 20 . Clinical stage was the most commonly reported risk factor for cancer recurrence 19 , 21 , 22 , our study results showed that patients with clinical stage II had 1.73 times the risk of recurrence, and patients with stage III or IV had 2.04 times the risk compared to those with clinical stage I.…”
Section: Discussionsupporting
confidence: 89%
“…In order to explore the disease process of organs, tissues or cells, some pathomorphological examination method can be used to examine their lesions, discuss the causes, pathogenesis and development process of lesions, and nally make pathological diagnosis (Murakami et al 2020). Pathological examination has been widely used in clinical work and scienti c research (Baraban et al 2020).…”
Section: Pathological Analysismentioning
confidence: 99%
“…These risk factors identi ed have also been reported by previous studies. 4,20 Clinical stage was the most commonly reported risk factor for cancer recurrence, 19,21,22 our study results showed that patients with clinical stage II were had 1.52 times the risk of recurrence, and patients with stage III or IV had 1.84 times the risk compared to those with clinical stage I. Patients with advanced clinical stages in general have a greater range of cancer lesions, and a higher probability of peripheral invasion and lymph node metastasis, thus even if the patient was systematically treated, the possibility of recurrence for these patients was relatively higher.…”
Section: Discussionmentioning
confidence: 99%